(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
The purpose of this paper is to understand, through fashion houses and 19th century dressmakers, the relationship between white women, property rights and women’s work in Rio de Janeiro in the first half of the 19th century. From 1816 onwards, a series of French dressmakers and seamstress arrived in Brazil, causing an innovation in terms of Brazilian business and fashion. These French women, as well as some Brazilian women, opened establishments and established their stores on the outskirts of the famous Rua do Ouvidor. However, not all women had the right to open a business, married women were denied the right to own property; in this sense, we aim to problematize the notion of women owners and their civil status and the way they were structuring their businesses in the Brazilian court, making the business related to clothing arousing the interest of society and becoming more and more inserted in the economic and social logistics of the period.